Relatório de sustentabilidade: uma proposta de indicadores para a Universidade Tecnológica Federal do Paraná - UTFPR - Durski, Danilo (2019)
Given society's growing concern about issues such as sustainability and social responsibility, it is possible to see an increasing number of organizations, both public and private, that have began to pay more attention to the publication of the sustainability report. Thus, the objective of this paper is to identify which are the most important performance indicators for a public educational institution, considering the items that make up the Ethos, IBASE and GRI reports. For that, through a bibliographic and descriptive research, by deductive method, the integrating indicators of the three previously mentioned reports were listed, proceeding to its comparative analysis considering their positive and negative points for applicability in a public institution of higher education, taking as scenario the Federal University of Technology - Paraná - UTFPR, seeking to demonstrate the practical application of the indicators chosen and their possible impacts for the strategic management of the institution.